SYNTHESIS AND CHARACTERIZATION OF SnO2/ZnO COMPOSITE USING JAPANESE PAPAYA LEAF EXTRACT (Cnidoscolus aconitifolius) WITH HYDROTHERMAL METHOD - Puspita, Heni; Agustin, Rika; Asdim; Angasa, Eka; Maryanti, Evi; Martono Hadi Putranto, Agus (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2024)
SnO2/ZnO composites were synthesized using the hydrothermal method using Japanese papaya (Cnidoscolus aconitifolius) leaf extract. This study aims to determine the effect of using Japanese papaya leaf extract (Cnidoscolus aconitifolius) on the formation of crystallinity and morphology in synthesizing SnO2/ZnO composites. Synthesis was carried out with variations in mass of 5, 10, and 15 grams using the hydrothermal method for 12 hours at 160°C. The results of X-Ray Diffraction (XRD) characterization show that wide diffractogram peaks are identified as the peaks of the SnO2 compound with a tetragonal structure and sharp peaks are identified as the peaks of the ZnO compound. The Fourier Transform Infrared (FTIR) characterization shows the peak wave number of 665 cm-1 which is the Sn-O-Sn strain and the peaks at wave numbers 598 cm-1 and 501 cm-1 which are the Zn-O strain. Characterization of Scanning Electron Microscopy (SEM) in the synthesis of SnO2/ZnO composites after adding Japanese papaya (Cnidoscolus aconitifolius) leaf extract had relatively reduced particle size and aggregate formation compared to no extract. The best effective mass of Japanese papaya leaf extract (Cnidoscolus aconitifolius) is the mass variation of 15 grams with 28.49 nm crystals.